JENIS-JENIS KATAK (AMPHIBI: ANURA) DI DESA SUKA MAJU KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU PROVINSI RIAU - Anisa, Susan; Purnama, Arief Anthonius; Karno, Ria (Sainstek : Jurnal Sains dan Teknologi, 2018)
This research aims to determine the diversity of frog (Amphibians: Anura) in Desa Suka Maju Kecamatan Tambusai Kabupaten Rokan Hulu. This study was conducted from February to April 2018 by using visual encounter survay (capture directly to the survey) by the sampling technique samples by random sampling. Samples were collected with three repetitions at each station. The results, is three family, seven genera and eight species are Kaloula baleata, Rhacophorus margaritifer, Polypedates leucomystax, Humerana miopus, Chalcorana chalconata, Hylarana erythraea, Fejervarya limnocharis and Fejervarya cancrivora.